Expression Levels of miR-590-3p in Hepatocellular Carcinoma and Osteosarcoma Cell Lines and its Downstream Target Genes - Elfar, Mennatallah Mohamed Bassem Mahmoud (AUC Knowledge Fountain, 2020)
Small non-coding RNA (miRNA) sequences of around 18-25 nucleotides can regulate different cellular pathways by acting on tumor suppressors, oncogenes or both. They are mostly tissue-specific and can be up-regulated or down-regulated, depending on the cancer or the tissue in which they are found. hsa-miR-590-3p was found to be involved in several types of cancers. In this study, we used computational analysis to identify potential downstream target genes of hsa-miR-590-3p. We used five databases (TargetScan, miRanda-mirSVR, miRDB, miRTarBase and Diana Tools) to obtain a dataset of potential downstream target genes of hsa-miR-590-3p from each database. We obtained lists of hundreds of genes from these databases. We obtained a shorter list of common genes in all five databases from which we selected fourteen genes with the potential to affect cancer progression and to help further understand the disease pathogenesis, based on previous literature and further in silico analysis using Expression Atlas and The Human Protein Atlas. SOX2, N-cadherin, E-cadherin and FOXA2 were utilized as potential downstream target genes of hsa-miR-590-3p. SNU449 and HepG2, hepatocellular carcinoma cell lines, and U2OS, osteosarcoma cell line, were used to carry out various molecular techniques to further validate our in silico results. mRNA and protein expression levels of these genes were detected using RT-PCR and western blotting respectively. In an attempt to co-localize the hsa-miR-590-3p and its candidate downstream target gene, SOX2, we conducted a miRNA in situ hybridization combined with immunohistochemistry staining using anti-SOX2. The results show that there is an inverse correlation between hsa-miR-590-3p expression and SOX2 protein expression in SNU449 and U2OS. Examining the expression of hsa-miR-590-3p downstream target genes can enhance our understanding of the cancer pathogenesis and how it can be utilized as a therapeutic tool.